Directly Spun Epoxy‐Crosslinked Polyethylenimine Fiber Sorbents for Direct Air Capture and Postcombustion Capture of CO2. Issue 9 (4th September 2022) - Wilfong, Walter C.; Wang, Qiuming; Ji, Tuo; Baker, James S.; Shi, Fan; Yi, Shouliang; Gray, McMahan L.
Abstract : Directly injected/spun fiber sorbents synthesized from solvent‐stable, crosslinked, immobilized amine sorbents remove CO2 under direct air capture (400 ppm CO2 ) and postcombustion (14% CO2 ) capture conditions. Scalable fiber sorbents are a key milestone toward a viable hollow fiber rapid temperature swing adsorption system. More details can be found in article number 2200356, Walter C. Wilfong, Shouliang Yi and co‐workers.